INVASIVE FUNGAL INFECTION IN CHILDREN WITH ACUTE LEUKEMIA AND SEVERE APLASTIC ANEMIA - Sutatta Supatharawanich; Nattee Narkbunnam; Nassawee Vathana; Chayamon Takpradit; Kamon Phuakpet; Bunchoo Pongtanakul; Sasima Tongsai; Phakatip Sinlapamongkolkul; Popchai Ngamskulrungroj; Wanatpreeya Phongsamart; Kleebsabai Sanpakit; Jassada Buaboonnam (Mediterranean Journal of Hematology and Infectious Diseases)
Although the outcome of childhood leukemia and severe aplastic anemia (SAA) has improved, infectious complications are still the major concern, particularly invasive fungal infection (IFI), which is one of the most common causes of infectious related death in such patients with prolonged neutropenia.  A retrospective study of IFI in pediatric patients with newly diagnosed and relapsed acute leukemia and SAA in Siriraj Hospital, Mahidol University, Thailand, was conducted.   There were 241 patients (150 patients with ALL, 35 patients with AML, 31 patients with relapsed leukemia and 25 patients with SAA) with the median age of 5.4 years (rage, 0.3-16.0 years). The overall prevalence of IFI was 23.2%, and the breakdown prevalence in ALL, AML, relapsed leukemia and SAA were 12.7%, 37.1%, 45.2% and 40.0% respectively. Candida tropicalis was the most common identifiable organism. Pulmonary IFI caused by invasive aspergillosis was the most common site of infection. The overall case-fatality rate was 50.0% with the highest rate in relapsed leukemia of 92.9%. In multivariable analysis, the age > 4 years, AML, relapsed leukemia and SAA were found to be independent risk factors of IFI with adjusted odds ratio of 2.3, 4.1, 5.1 and 3.7 respectively. In SAA group, only very severe aplastic anemia (ANC < 200 mm3) was found to be associated with development of IFI with odds ratio of 32.7. IFI in Thai children with hematologic diseases appeared to be prevalent with high fatality. Anti-fungal prophylaxis should be considered in patients with SAA to prevent IFI.